Cytomegalovirus Infections in Hematopoietic Stem Cell Transplant: Moving Beyond Molecular Diagnostics to Immunodiagnostics - Chhavi Gupta; Netto George Mundan; Shukla Das; Arshad Jawed; Sajad Ahmad Dar; Hamad Ghaleb Dailah (Diagnostics, 2024)
Human CMV, regularly reactivated by simple triggers, results in asymptomatic viral shedding, powerful cellular immune responses, and memory inflation. Immunocompetent individuals benefit from a robust immune response, which aids in viral management without causing clinically significant illness; however, immunodeficient individuals are always at a higher risk of CMV reactivation and disease. Hematopoietic stem cell transplant (HSCT) recipients are consistently at higher risk of CMV reactivation and clinically significant CMV illness due to primary disease, immunosuppression, and graft vs. host disease. Early recovery of CMV-CMI responses may mitigate effects of viral reactivation in HSCT recipients. Immune reconstitution following transplantation occurs spontaneously and is mediated initially by donor-derived T cells, followed by clonal growth of T cells produced from graft progenitors. CMV-specific immune reconstitution post-transplant is related to spontaneous clearance of CMV reactivation and may eliminate the need for prophylactic or pre-emptive medication, making it a potential predictive marker for monitoring CMV reactivation. This review highlights current thoughts and therapeutic options for CMV reactivation in HSCT, with focus on CMV immune reconstitution and post-HSCT monitoring. Immune monitoring aids in risk stratification of transplant recipients who may progress from CMV reactivation to clinically significant CMV infection. Implementing this approach in clinical practice reduces the need for periodic viral surveillance and antiviral therapy in recipients who have a high CMV-CMI and thus may experience self-limited reactivation. Therefore, in the age of precision medicine, it is critical to incorporate CMV-specific cellular immune surveillance into conventional procedures and algorithms for the management of transplant recipients.